Composition portfolio - Webb, Cassidy Frank (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2006)
Introduction: This portfolio consists of musical ideas which I have had for some time now. I have attempted to capture these ideas throughout the portfolio, starting with the smaller works (Brumes et Pluies) and building up to the larger works (James Tiberius, The tide). Brumes et Pluies is minimalistic in style. The interlocking of the two pianos plays an important role in the texture of the piece. The rhythms are repetitive throughout, with only slight variations. Kalahari is more idiomatic, rhythmical and has a main theme which recurs throughout the piece. Melodic fragments are used, sometimes with slight variations. This piece was inspired by the Kalahari desert, with its abundance of life. I enjoy the string quartet because of the homogeneity of sound on the one hand, and the diversity possible by using different techniques and effects on the other. James Tiberius is a work for chamber orchestra. Motifs in the music resemble certain animals. The rhythm is unstable, as is the harmony. There are many melodic fragments throughout. The texture is thin in certain areas (at the beginning) and dense in others (the waltz). The harmony is sometimes unconventional. The Tide was written in response to a memory of a drowning incident I experienced when I was a child. This orchestral piece is strong in form. The opening, for example, is tense and slightly atonal in harmony. The pomposo section tends to utilise most of the orchestra, so the texture is a lot denser here and the harmony is more conventional. I try not to use traditional forms in my composition. Rather, I prefer to compose by re-using and re-introducing ideas as I proceed.
Keywords: Uncatalogued